Novel reporter system to monitor early stages of the hepatitis B virus life cycle. Issue 11 (16th October 2015) - Nishitsuji, Hironori; Ujino, Saneyuki; Shimizu, Yuko; Harada, Keisuke; Zhang, Jing; Sugiyama, Masaya; Mizokami, Masashi; Shimotohno, Kunitada
Abstract : A recombinant hepatitis B virus (HBV) expressing NanoLuc (NL) (HBV/NL) was produced by cotransfecting a plasmid containing a 1.2‐fold HBV genome carrying the NL gene with a plasmid bearing a packaging‐defective 1.2‐fold HBV genome into a human hepatoma cell line, HepG2. We found that NL activity in HBV/NL‐infected primary hepatocytes or sodium taurocholate cotransporting polypeptide‐transduced human hepatocyte‐derived cell lines increased linearly for several days after infection and was concordant with HBV RNA levels in the cells. Treatment of the virus‐infected cells with HBV inhibitors reduced NL activity in a dose‐dependent manner. Detection of HBV/NL infection, monitored by NL activity, was highly sensitive and less expensive than detection using the conventional method to evaluate HBV infection. In addition, because we also studied host factors, this system is applicable not only for studying the HBV life cycle, but also for exploring agent(s) that regulate HBV proliferation. Abstract : We produced a novel reporter‐based HBV that supports the early stages of HBV life cycle. By using this system we identified host factors that affect HBV infection/replication. This system will be used for large‐scale screening and development of low molecular weight agents that affect HBV replication and will contribute to the development of novel, innovative therapeutic agents of which suppress and eliminate HBV.